Retinal Microvascular Reactivity in Chronic Cigarette Smokers and Non-smokers: An Observational Cross-Sectional Study - Xu, Huan; Zong, Yuan; Yu, Jian; Jiang, Chunhui; Zhu, Haohao; Sun, Xinghuai (Frontiers in Medicine, 2021)
Purpose: To evaluate the changes in the retinal microvasculature and its reactivity in chronic cigarette smokers. Methods: Thirty-four male chronic cigarette smokers and 18 male non-smokers were enrolled. Optical coherence tomography angiography was used to measure the perfused retinal vessel densities (PVDs) of the peripapillary and parafoveal areas at baseline and during phase IV of the Valsalva maneuver (VM-IV). Systemic blood pressure and intraocular pressure were also measured. Results: The baseline PVD in the peripapillary area of the smokers was significantly lower than the non-smokers (59.56 ± 2.26% vs. 61.67 ± 3.58%, respectively; P = 0.005). However, there was no significant difference in the foveal avascular zone or parafoveal PVD between the two groups. During VM-IV, the peripapillary PVD of the smokers decreased by 1.13 ± 3.50%, which was significantly less than that of the non-smokers (−3.83 ± 4.26%, P < 0.05). Similarly, the parafoveal PVD of the smokers decreased by 5.49 ± 9.70%, which was significantly less than the percentage change of the non-smokers (−13.01 ± 8.39%, P < 0.05). There was no significant difference in the percentage change in systemic blood pressure parameters between the two groups. Conclusion: The retinal microvasculature and its reactivity were impaired in chronic smokers compared with non-smokers. The extent of impairment differed among different regions of the fundus.